Soft body impact resistance of composite foam core sandwich panels with unidirectional corrugated and tubular reinforcements. (October 2019) - Vignjevic, Rade; Campbell, James; Hughes, Kevin; Orłowski, Michał; Garcea, Serafina; Withers, Philip; Reed, Julian
Highlights: Composite sandwich panels with unidirectional core reinforcement subjected to soft body high velocity impact Computed tomography (CT) damage assessment of composite panels Coupled FE – SPH impact modelling Improved damage resistance of foam core sandwich panels with core reinforcement Potential for application of core reinforced composite sandwich panels in aerospace Abstract: Bird strikes represent a major hazard in the lifecycle of composite aircraft components, due to the low impact resistance of composites. The research presented in this paper investigates soft body impact performance of composite sandwich panels with corrugated and tubular core reinforcements. This type of panel with augmented strength and stiffness in one direction is of high importance for specific aerospace applications. The panels were subjected to high velocity impact with soft gelatine projectile as used in bird strike tests. In addition, the experimental part included non-destructive inspections of the sandwich panel samples. Panel performance was also analysed with the non-linear transient analysis software LS-DYNA with finite element and SPH capability. The panel with corrugated reinforcement showed good impact resistance with damage restricted to the impacted face sheet, foam core and corrugated reinforcement. The panel with tubular reinforcement, of the same thickness, did not suffer any damage at the same impact velocity of 115 m/s, but was damaged at a higher impact velocity of 235 m/s. The numerical studies helped to understand the experimental data, enabling comparison of impact performance of the reinforced sandwich panels and a benchmark conventional sandwich panel. The proposed reinforced sandwich panels, with the desired augmented strength and stiffness in one direction, showed improved impact resistance in comparison to conventional sandwich panels and therefore have potential for application in aerospace structures where these properties are desirable.